Evaluation Of Cbr Improvement For Cohesive Soil Used As A Subgrade Using A Mix Of Fill Sand And Lime - Lucky Amperawan S.; Felix Setiawan; Nisrina Nadhifah (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
The results indicated that both lime and cement stabilization significantly improved the CBR value compared to the untreated soil, which did not satisfy the Bina Marga minimum requirement for subgrade material (CBR < 6%). The addition of 4% lime and 4% loose sand increased the CBR value to 6.40%, meeting the minimum specification. Meanwhile, the combination of 4% cement and 4% loose sand resulted in a substantially higher CBR value of 15.50%, demonstrating superior technical performance. Although cement provided greater strength improvement, lime remained a cost-effective alternative capable of enhancing soil stability. Furthermore, a comparison between laboratory and field CBR values showed that laboratory results tended to be higher due to more controlled testing conditions. These findings demonstrate the potential of soil stabilization using lime or cement combined with loose sand to improve the engineering properties of saturated cohesive soils for road subgrade applications